Tooth fragment re-attachment in an incompletely formed root: A case report with literature review - Shivesh Acharya; Shruti Singh; Sarabjot Kaur Bhatia (Wolters Kluwer Medknow Publications, 2020)
Coronal fractures of anterior teeth are the most common form of dental trauma that occur in children and adolescence. They cause functional, aesthetics and psychological problems for both their children and parents. Intact tooth fragment provides a very conservative approach for reattachment of dental fragment. Owing to its good long lasting aesthetics (as tooth's original anatomic form, color and surface texture are maintained) and functional restorability it provides a better alternative as compared to the resin based composite or crown restoration. It overcomes the problem of repeated reconstruction of composite with age and provides a positive psychological response. The article reports a case of a child with anterior tooth fracture that was successfully treated using tooth fragment reattachment. It aims to review and discuss the methodology along with different preparation techniques and adhesives used by various authors and analyze the advancement and most accepted procedure for of the treatment. It also highlights the shortcomings of the technique as patient cooperation determines the prognosis of the procedure and a long term follow up determines the success of the procedure.